Menstrual Health issues and their Impact on Quality of life: A study among college going girls in Lucknow, Uttar Pradesh - Bajpai, Maitri; kumar, Anil; Kumar Bajpai, Prashant (Journal of Neonatal Surgery, 2025)
Menstrual health is a critical aspect of women's well-being, particularly for college students who face academic pressures and social challenges. Menstrual morbidities, such as dysmenorrhea (painful menstruation), menorrhagia (heavy menstrual bleeding), and premenstrual syndrome (PMS), are prevalent among young women and can significantly affect their quality of life (QoL). This study aims to assess the prevalence and impact of these menstrual conditions on the daily lives of college girls, focusing on academic performance, physical health, emotional well-being, and social interactions. The research also investigates the coping mechanisms employed by students and the barriers they face in accessing appropriate medical care and treatment. A cross-sectional survey was conducted involving a sample of college girls of Lucknow, Uttar Pradesh. Self-administered questionnaires were used to gather data on menstrual history, symptoms, and their effects on QoL. The findings revealed that dysmenorrhea was the most commonly reported menstrual morbidity, followed by PMS. A significant proportion of participants reported that their menstrual issues affected their academic performance, physical health, and social engagement, with many students missing classes or experiencing reduced concentration during their periods. Emotional distress, such as mood swings and irritability, also emerged as a common issue, negatively impacting mental health and social relationships. The study further highlighted that while many students used over-the-counter medications to manage pain, a substantial number faced challenges in seeking medical advice due to stigma, lack of time, and insufficient knowledge about available treatments. The study emphasizes the need for greater awareness, better healthcare access, and supportive policies in educational institutions to improve the menstrual health and overall well-being of college girls. The results underscore the importance of addressing menstrual health not just as a physical issue, but as a factor that influences broader aspects of students' academic and personal lives.